2023
DOI: 10.3389/fnmol.2022.1019173
|View full text |Cite
|
Sign up to set email alerts
|

Very early environmental enrichment protects against apoptosis and improves functional recovery from hypoxic–ischemic brain injury

Abstract: Appropriate rehabilitation of stroke patients at a very early phase results in favorable outcomes. However, the optimal strategy for very early rehabilitation is at present unclear due to the limited knowledge on the effects of very early initiation of rehabilitation based on voluntary exercise (VE). Environmental enrichment (EE) is a therapeutic paradigm for laboratory animals that involves complex combinations of physical, cognitive, and social stimuli, as well as VE. Few studies delineated the effect of EE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…Many physiological factors including physical activities, environmental situations, cognitive functions and aging can affect neurogenesis in the hippocampus ( Stappert et al, 2018 ). Environmental enrichment activates the cell cycle, induces neurogenesis, and increases neuronal survival in the hippocampus ( Barak et al, 2013 ; Zhao and Moore, 2018 ; Lee et al, 2023 ). Evidently, miRNA expression profile in the hippocampus undergoes relatively large changes following exposure to an enriched environment ( Barak et al, 2013 ).…”
Section: Micrornas and Neurogenesis In The Hippocampusmentioning
confidence: 99%
“…Many physiological factors including physical activities, environmental situations, cognitive functions and aging can affect neurogenesis in the hippocampus ( Stappert et al, 2018 ). Environmental enrichment activates the cell cycle, induces neurogenesis, and increases neuronal survival in the hippocampus ( Barak et al, 2013 ; Zhao and Moore, 2018 ; Lee et al, 2023 ). Evidently, miRNA expression profile in the hippocampus undergoes relatively large changes following exposure to an enriched environment ( Barak et al, 2013 ).…”
Section: Micrornas and Neurogenesis In The Hippocampusmentioning
confidence: 99%
“…Over the past decade, impressive effects of EE have also been identified in other brain diseases such as AGING Huntington's disease (HD) [9], Alzheimer's disease (AD) [10,11] and various forms of brain injury. Besides, many studies have shown that EE has a positive effect on the stroke [12][13][14]. For instance, EE increased the proliferation of hippocampal and cortical endothelial cells [15], improved the survival rate of newborn astrocytes [16], decreased growth inhibitory molecules [17], induced neural plasticity [18] and promoted the formation of neovascularization in cerebral ischemia rats [19].…”
Section: Introductionmentioning
confidence: 99%